A mission for development : Utah universities and the Point Four Program in Iran - Garlitz, Richard P. (Utah State University Press, 2018)
"A story of technical advisors from three Utah universities who worked in Iran as part of the Point Four Program. Using their experiences, the book reexamines the rise and fall of the US-Iranian alliance and the roles that American universities played in international development during Cold War"--Provided by publisher